Environmental Accounting and ESG Integration in Hungary’s Energy Sector: A Study of the Top Corporations and their Subsidiaries - Kecskés, Alexa; Kozma, Dorottya Edina (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study investigates environmental accounting, corporate sustainability, and ESG practices of the top energy sector companies (Mol Magyar Olaj- és Gázipari Plc., MVM Energetika Plc., E.On Hungária Energetikai Ltd., Veolia Energia Magyarország Plc., and their subsidiaries) in Hungary, selected based on the HVG Top 500 company ranking. The research focuses on how leading energy firms incorporate environmental considerations into their accounting systems and sustainability strategies in response to increasing regulatory, stakeholder, and market pressures. Emphasis is placed on the role of ESG reports and Notes to the financial statements as a key instrument of environmental accounting, as these disclosures provide critical qualitative and quantitative information on environmental liabilities, provisions, emissions-related risks, sustainability investments, and compliance with environmental regulations.  Using a qualitative content analysis of annual reports, sustainability reports, and ESG disclosures, the study evaluates the transparency, consistency, and depth of environmental information disclosed by the sampled companies. Findings reveal notable differences in the scope and quality of environmental and ESG reporting, especially regarding the use of Notes to enhance accountability and stakeholder understanding. The research contributes to the literature by highlighting the importance of financial statement disclosures in strengthening ESG credibility and supporting sustainable decision-making within the Hungarian energy sector.